Sh3tc2 deficiency affects neuregulin‐1/ErbB signaling. Issue 7 (2nd April 2013) - Gouttenoire, Estelle Arnaud; Lupo, Vincenzo; Calpena, Eduardo; Bartesaghi, Luca; Schüpfer, Fanny; Médard, Jean‐Jacques; Maurer, Fabienne; Beckmann, Jacques S.; Senderek, Jan; Palau, Francesc; Espinós, Carmen; Chrast, Roman
<x xml:space="preserve">Abstract</x> Mutations in SH3TC2 trigger autosomal recessive demyelinating Charcot‐Marie‐Tooth type 4C (CMT4C) neuropathy. Sh3tc2 is specifically expressed in Schwann cells and is necessary for proper myelination of peripheral axons. In line with the early onset of neuropathy observed in patients with CMT4C, our analyses of the murine model of CMT4C revealed that the myelinating properties of Sh3tc2‐deficient Schwann cells are affected at an early stage. This early phenotype is associated with changes in the canonical Nrg1/ErbB pathway involved in control of myelination. We demonstrated that Sh3tc2 interacts with ErbB2 and plays a role in the regulation of ErbB2 intracellular trafficking from the plasma membrane upon Nrg1 activation. Interestingly, both the loss of Sh3tc2 function in mice and the pathological mutations present in CMT4C patients affect ErbB2 internalization, potentially altering its downstream intracellular signaling pathways. Altogether, our results indicate that the molecular mechanism for the axonal size sensing is disturbed in Sh3tc2‐deficient myelinating Schwann cells, thus providing a novel insight into the pathophysiology of CMT4C neuropathy.